Kebangkitan Kesultanan Ternate pada Era Reformasi 1998-2002 - Rustam Hasim; Oktosiyanti MT Abdullah; Siti Rahia H. Umar (Universitas Islam Negeri Alauddin Makassar, 2019)
The elite revival of the Ternate Sultanate after the New Order illustrated how the palace group played a new role in staying in its position as a clan of power in the local sphere. In this case, the emergence of the elite of the Ternate Sultanate can be understood and interpreted in three respects. First, the rise of feudalistic power in the region to strengthen political position stemmed from cultural construction based on history and genealogical similarities. Second, the individual revival of the Sultan of Ternate MudafarSyah in the name of the Sultanate institution as his political vehicle. Third, there is the elite desire of the Ternate Sultanate to be more institutionally accommodated into the formal government political stage. This reality shows the political participation of the Ternate Sultanate in the post-independence domain of local politics until now, is an important field of historical research. As a historical phenomenon, the process of dynamics of local politics like this is interesting to study, because the Sultan of Ternate has long been a part of the history of politics in North Maluku. Also, there is an implicit message about how partial Indonesian political studies are if they only focus on the dynamics of national politics. In the case, there are several national political issues which can initially be pursued from the region and vice versa Kebangkitan elite Kesultanan Ternate pasca-Orde Baru mengambarkan bagaimana kelompok istana memainkan peran baru agar tetap berada pada posisinya sebagai pengenggam kekuasaan di ranah lokal. Dalam hal ini, apat dipahami bahwa ada tiga faktor yang menyebabkan kemunculan elit Kesultanan Ternate Pertama, bangkitnya kekuasaan feodalistik di daerah untuk memperkuat posisi politik bersumber dari konstruksi budaya yang berbasiskan pada sejarah masa lalu maupun kesamaan genealogis. Kedua, kebangkitan secara individual Sultan Ternate Mudafar Syah dengan mengatasnamakan institusi kesultanan sebagai kendaraan politiknya. Ketiga, adanya keinginan elite Kesultanan Ternate untuk lebih diakomodasikan secara institusional ke dalam panggung politik pemerintahan formal. Realitas tersebut menunjukkan partisipasi politik Kesultanan Ternate dalam ranah politik lokal pasca-kemerdekaan hingga kini, merupakan sebuah bidang penelitian sejarah yang penting. Sebagai sebuah fenomena historis, proses dinamika politik lokal seperti ini menarik untuk diteliti, karena telah sejak lama para Sultan Ternate menjadi bagian dalam sejarah perpolitikan di Maluku Utara. Selain itu, ada sebuah pesan implisit tentang betapa parsialnya kajian politik Indonesia bila hanya memfokuskan pada dinamika politik nasional saja. Pada hal ada beberapa persoalan politik nasional yang awalnya dapat diruntut dari daerah dan begitu pula sebaliknya.